Measuring Exposure to Risk in Global Value Chains - Borin, Alessandro; Mancini, Michele; Taglioni, Daria (World Bank, Washington, DC, 2021)
How exposed are countries and sectors to GVC risks? GVC participation matters for answering this question. Standard approaches either overstate the degree of backward integration or underestimate the involvement of some industries, especially services, in Global Value Chain (GVC) activity. To correct these biases, this paper proposes a novel comprehensive method to measure GVC participation using Inter-Country Input-Output (ICIO) linkages in both trade and output and shows that these improvements in methodology matter from a macroeconomic perspective. GVC integration, as measured by the indicators, decreases the exposure to domestic shocks and increases that to global shocks. The paper also finds that exposure to shocks is complex: in most countries and sectors, output is simultaneously exposed to supply and demand shocks. This two-sided exposure suggests that disruptions may not be easily managed by unilateral policy attempts at forcing a reorganization of buyers-seller relationships.